Effect of Low-Frequency Ultrasonic-Assisted Enzymolysis on the Physicochemical and Antioxidant Properties of Corn Protein Hydrolysates - Qiufang Liang; Xiaofeng Ren; Haile Ma; Suyun Li; Kangkang Xu; Ayobami Olayemi Oladejo (Journal of Food Quality)
The aim of this study was to investigate the effect of low-frequency ultrasound on the enzymolysis of corn protein. A L9 (34) orthogonal design was used to optimize ultrasound pretreatment conditions. Degree hydrolysis (DH), conversion rate of protein (CR), and DPPH IC50 were selected as analytical indicators. Under the optimal ultrasound conditions (5 W/L power, 2 s/2 s on/off time, 50°C temperature, and 25 min time), the DH, CR, and radical (DPPH∙, OH∙) scavenging capacities were significantly increased. Molecular weight distribution and amino acid profile analysis showed that ultrasound pretreatment enhanced the formation of short-chain peptides with molecular weight of 200–3000 Da, especially the peptides containing hydrophobic amino acids. Moreover, 40 potential antioxidant peptides were purified by C18 semipreparative column and identified by UPLC-ESI-MS. The results suggest that the optimal ultrasonic-assisted enzymolysis technology could be useful for preparation of antioxidant peptides from corn.